Analysis of The Readiness of Electronic Medical Record Implementation Using DOQ-IT at Rsud Class D Pratama Sendawar - Venny Debora Yolanda; Purwadhi Purwadhi; Mira Veranita (Dinasti Publisher, 2025)
This study aims to evaluate the readiness of Class D Primary Hospital Sendawar in implementing Electronic Medical Records (EMR) using DOQ-IT, focusing on four aspects: human resources (HR), organizational work culture, governance and leadership, and technology infrastructure. The method used was qualitative through in-depth interviews with health workers and hospital staff, and thematic analysis. The results showed that HR had a positive understanding of the benefits of EMR, but lacked information technology skills and adequate training. Organizational work culture supports the implementation of EMR, but needs strengthening in the formation of special teams and policy development. Management support for EMR is strong, but a clear strategy for internal coordination is needed. Technology infrastructure is currently inadequate, with problems in hardware, software and internet networks. The research conclusions emphasize the need for increased HR training, policy development, and infrastructure improvements. RSUD Kelas D Pratama Sendawar is advised to adopt a comprehensive approach to managing change to facilitate an effective transition to the EMR system.